2009
DOI: 10.1039/b917013h
|View full text |Cite
|
Sign up to set email alerts
|

A quantum mechanical study of TiCl3α, β and γ crystal phases: geometry, electronic structure and magnetism

Abstract: The electronic structure of different magnetic states of alpha, beta and gamma modifications of TiCl(3) has been computed employing the density functional theory with periodic boundary conditions and localized Gaussian basis sets. The analysis of the density of the electronic states (DOS) and of the spin density makes it possible to classify these halides as Mott-Hubbard insulators, where the band gap appears a result of large on-site Coulomb interaction. For each crystalline phase, the relative stability of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 45 publications
3
5
0
Order By: Relevance
“…We tried to discriminate between the two possibilities by DFT theoretical calculations conducted on the same TiCl3 nano-cluster adopted to validate the EXAFS data analysis (Figure 1f). However, simulation of the XES of TiCl3 appeared to be very challenging, in line with the results reported in the study of Sementa et al, [46] and no decisive conclusions could be drawn from them. Therefore, at the present stage, we are not able to univocally assign the weak band at 4952 eV observed in the vtc-XES spectrum of TiMg treated in excess of TOAl.…”
Section: Introductionsupporting
confidence: 77%
“…We tried to discriminate between the two possibilities by DFT theoretical calculations conducted on the same TiCl3 nano-cluster adopted to validate the EXAFS data analysis (Figure 1f). However, simulation of the XES of TiCl3 appeared to be very challenging, in line with the results reported in the study of Sementa et al, [46] and no decisive conclusions could be drawn from them. Therefore, at the present stage, we are not able to univocally assign the weak band at 4952 eV observed in the vtc-XES spectrum of TiMg treated in excess of TOAl.…”
Section: Introductionsupporting
confidence: 77%
“…Magnetic measurements of bulk α-TiCl 3 flakes revealed an antiferromagnetic behavior below 265 K ( T N ) and an additional magnetic transition at 217 K that is accompanied by sharp changes in a and c lattice parameters. , Moreover, semiconducting properties were confirmed between 170 and 330 K . Later, further computational insights were given due to various density functional theory approaches . Yet, the experimentally observed physical properties of thin α-TiCl 3 sheets or even monolayer are still outstanding, including their catalytic properties.Calculations of two-dimensional TiCl 3 sheets propose half-metallicity with a band gap of 0.6 eV and a ferromagnetic character (in monolayer) with an estimated Curie temperature of 376 K …”
Section: Introductionmentioning
confidence: 99%
“…No magnetic order is present at 4 K, which is possibly explained by the formation of Ti–Ti bonds below the phase transition at 217 K . Cavallone et al performed electrical and optical measurements of α-TiCl 3 and found semiconducting behavior, and recent theoretical work showed that layered TiCl 3 polymorphs are Mott insulators . No experimental studies of TiCl 3 in the few-layer limit are reported, although Zhou et al predicted half metallicity in monolayer TiCl 3 and Geng et al predicted that TiY 3 are FM insulators …”
Section: Layered Transition Metal Halidesmentioning
confidence: 99%
“…803,804 The magnetic susceptibility has a broad maximum at 260 K (suggesting AFM order) that quickly drops below 217 K. 804 No magnetic order is present at 4 K, which is possibly explained by the formation of Ti−Ti bonds below the phase transition at 217 K. 805 Cavallone et al performed electrical 806 and optical 807 measurements of α-TiCl 3 and found semiconducting behavior, and recent theoretical work showed that layered TiCl 3 polymorphs are Mott insulators. 808 No experimental studies of TiCl 3 in the few-layer limit are reported, although Zhou 810 Multiple polytypes of FeCl 3 are reported at room temperature: BiI 3 -type, 811 as well as structures of space group P312 and R3. 812 FeCl 3 has been shown to have a HM ground state with the AFM coupled layers coupled below ∼9 K, 813,814 although a higher temperature of 15 K was reported in an early neutron diffraction study.…”
Section: Layered Transition Metal Halidesmentioning
confidence: 99%